Implementasi ISO-IEC 25010 untuk Analisis Kualitas Sistem Informasi Manajemen Kerja Praktik (SIM-KP) - Dewi, Rosanti; Satyareni, Diema Hernyka; Kurniawan, Eddy (Universitas Methodist Indonesia, 2025)
The rapid development of technology has influenced various sectors, including education, where technology supports academic processes such as the Internship Management Information System (SIM-KP) at Universitas Pesantren Tinggi Darul Ulum Jombang. Despite its benefits, several issues have been identified, such as user interface complexity and unused features, necessitating a quality analysis. This study aims to analysis the quality of SIM-KP using the ISO/IEC 25010 standard. Compared to other methods, ISO/IEC 25010 offers the most comprehensive approach to analysis software system quality, focusing on aspects such as usability, functional suitability, reliability, efficiency, security, portability, compatibility, and maintainability. Data collection was conducted through questionnaires distributed to 53 Information Systems students via WhatsApp, using a Likert scale for assessment criteria. The research results show an average quality score of 71.3%, categorized as good. Performance efficiency achieved the highest score (80.7%), followed by functional suitability (77.2%), while maintainability (65.2%) and usability (65.0%) scored lower. Other scores include security (70.2%), portability (74.3%), and compatibility (69.2%). These findings indicate that the eight variables of ISO/IEC 25010 used in the analysis of SIM-KP achieved a good score.